2015
DOI: 10.1097/cnq.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Research Into a Closed and Protected Place

Abstract: This article reports a Swedish research project designed to study the impact of a cyclic light system, sound absorbents, and selected interior design changes in rooms within an intensive care unit. The authors describe the limitations of many previously reported intensive care unit (ICU) design research projects, and believe that much more knowledge is needed, which reflects a multidisciplinary perspective. It is complicated to carry out intervention research in ICUs because of the condition of patients, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…As expected, there were some limitations that must be considered. It is challenging to conduct research in an ICU setting (Lindahl & Bergbom, ). Varied factors, such as busy wards and ICU nurses being unable to leave their duties, resulted in sample size problems.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, there were some limitations that must be considered. It is challenging to conduct research in an ICU setting (Lindahl & Bergbom, ). Varied factors, such as busy wards and ICU nurses being unable to leave their duties, resulted in sample size problems.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough preparation is required when utilising observation as a research method in order to collect optimal data, as the ICU is considered to be a place of limited access and interaction, where the dignity of patients must be protected (9,31). The first step is to gain access to the 'field' and to related situations.…”
Section: The Clinical Studymentioning
confidence: 99%
“…One or 20 observations can be selected depending on the study objective, number of participants and quality of the observations. Further, space and place (31) are issues of considerable importance when conducting an observation, as qualitative research always depends on the context. Therefore, it is necessary to consider how the room is arranged and if there is a suitable area with adequate space in which to sit without disturbing ongoing care activities.…”
Section: Preparing the Observation Sessions: Recommendationsmentioning
confidence: 99%
“…However, even though sound levels have been found to be high in ICUs, they could easily be improved through the use of sound absorbents behind walls and ceiling. When a patient room in an ICU was refurbished according to the principles of evidence-based research (Ulrich, 2006 ), and in order to communicate a song of caring and praise, restorative energies were conveyed to patients and their loved ones as well as to staff (Lindahl & Bergbom, 2015 ). The results showed that both patients and visitors evaluated the cyclic light system as comfortable (Engwall et al, 2014 , 2015 ).…”
Section: Some Examples and Experiences From Our Own Researchmentioning
confidence: 99%